Mitral valve replacement for mitral stenosis caused by Libman-Sacks endocarditis. - Vaughton, K C (1979)
A women who developed mitral stenosis from Libman-Sacks endocarditis is described. The mitral valve was replaced by a Starr-Edwards prosthesis. One year later, despite her being maintained on steroids and azathioprine, the verrucous endocarditis progressed to cause sudden, severe dysfunction of the prosthetic valve.